Progam Tatanen Di Bale Atikan Oleh Mahasiswa PLSP UPI Kampus Purwakarta Di SDN 2 Munjul Jaya - Rayi Djaya Laksmana; Dwi Ajeng Puspitaningrum; Annisa Muthmainnah; Fitri Fitriah; Luthfi Oktavia; Yeni Amelia (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Character education is an effort to build individuals to become good individuals who can benefit themselves and their environment. One form of breakthrough made by the government to implement Character Education makes Strengthening Character Education (PPK), where the program is aimed at schools in Indonesia, starting from early childhood to high school levels. Purwakarta Regency also implemented a program created by the government by applying it to farming activities. The program was named Tatanén di Balé Atikan. It is a program launched by the Purwakarta district government to build character through activities to preserve the environment. This program is prepared for students as a form of protecting the environment. This article discusses students' dedication to the school environment in carrying out a government program, Tatanén di Balé Atikan at UPTD SDN 2 Munjul Jaya. The program at this school aims to raise awareness of caring for, protecting, and preserving the surrounding environment. This program utilizes plastic waste to be employed as decoration as well as community service to clean up the environment. This activity is carried out as a community service to organize the school environment and create an ornamental garden by utilizing used goods such as greening. The Program results are expected to make school residents grow a sense of love for the environment and also maintain cleanliness.